Análise comparativa da produtividade dos sistemas construtivos de alvenaria de vedação: bloco cerâmico e bloco de gesso. - Oliveira, Bárbara Paniquar de Souto (2019)
The quest for increasing productivity in construction companies is evident due to the need of improving efficiency, reducing costs and improvement of final product quality. These needs can come from good knowledge and management of productivity on the site, not to mention the reduction in the consumption of project resources. This thesis aims to make a comparative analysis of productivity indices between execution of masonry, through a case study in six construction sites in Pernambuco, all from a big construction company, with emphasis on wall execution in ceramic block and gypsum block. Therefore, two main construction indicators were observed: Productivity Unitary Ratio and Loss of Labor Productivity. After cumulative Productivity Unitary Ratio for the 6 work sites the obtained result for ceramic block walls was an average of 0.47 person-hours /m², while for gypsum block wall the average Productivity Unitary Ratio was person-hours /m². This way, the gypsum block showed a better efficiency when compared to ceramic block through the analysis of loss of labor productivity, 10% and 6%, respectively. It was possible then to conclude that the gypsum block presented a 15% higher productivity when compared to the ceramic block on wall execution.